Impact of the superior cavopulmonary anastomosis on cerebral oxygenation. (16th March 2020) - Thatte, Nikhil; Zhou, Lingyu; Kheir, John N.
Abstract: Background: Patients with univentricular heart disease may undergo a superior cavopulmonary anastomosis, an operative intervention that raises cerebral venous pressure and impedance to cerebral venous return. The ability of infantile cerebral autoregulation to compensate for this is not well understood. Materials and methods: We identified all patients undergoing a superior cavopulmonary anastomosis (cases) and compared metrics of cerebral oxygenation upon admission to the ICU with patients following repair of tetralogy of Fallot or arterial switch operation (controls). The primary endpoint was cerebral venous oxyhaemoglobin saturation measured from an internal jugular venous catheter. Other predictor variables included case–control assignment, age, weight, sex, ischemic times, arterial oxyhaemoglobin saturation, mean arterial blood pressure, and superior caval pressure. Results: A total of 151 cases and 350 controls were identified. The first post-operative cerebral venous oxyhaemoglobin saturation was significantly lower following superior cavopulmonary anastomosis than in controls (44 ± 12 versus 59 ± 15%, p < 0.001), as was arterial oxyhaemoglobin saturation (81 ± 9 versus 98 ± 5%, p < 0.001). Cerebral venous oxyhaemoglobin saturation correlated poorly with superior caval pressure in both groups. When estimated by linear mixed effects model, arterial oxyhaemoglobin saturation was the primary determinant of central venous oxyhaemoglobin saturation in both groups (β = 0.79, p = 3 × 10 −14 ); for every 1% point increase in arterial oxyhaemoglobin saturation, there was a 0.79% point increase in venous oxyhaemoglobin saturation. In this model, no other predictors were significant, including superior caval pressure and case–control assignment. Conclusion: Cerebral autoregulation appears to remain intact despite acute imposition of cerebral venous hypertension following superior cavopulmonary anastomosis. Following superior cavopulmonary anastomosis, cerebral venous oxyhaemoglobin saturation is primarily determined by arterial oxyhaemoglobin saturation.